PERAN KANTOR KEMENTERIAN AGAMA KECAMATAN MALILI DALAM MENINGKATKAN TOLERANSI ANTARUMAT BERAGAMA DI KABUPATEN LUWU TIMUR - Jeni Bulo' Saladan; Naomi Naomi (Adisam Publisher, 2025)
This study aims to analyze the strategic role of the Malili District Ministry of Religious Affairs Office in enhancing interfaith tolerance in East Luwu Regency. The background of this research is the social reality of the multicultural and multireligious Malili community, which demands wise, inclusive, and contextual management of interfaith relations. Using a descriptive qualitative approach, data was collected through interviews, observation, and documentation, which were then analyzed through data reduction, data presentation, and conclusion drawing techniques. The results show that the Malili Ministry of Religious Affairs Office plays a significant role through harmony development programs, facilitation of the Interfaith Harmony Forum (FKUB), tolerance cadre training, and interfaith cultural activities. However, challenges such as low religious literacy, group exclusivism, and the influence of digital disinformation remain major obstacles to realizing comprehensive tolerance at the grassroots level. Collaborative strategies and cultural approaches based on local values ​​have proven to be effective in building a peaceful, inclusive, and sustainable social space. These findings emphasize the importance of synergy between the state and civil society in managing religious diversity positively and productively.